Skip-beat! 10 - Nakamura, Yoshiki (Shojo beat manga., 2008)
Kyoko gets a big break when she is scouted for the role of Mio, a young woman with a terribly scarred face, in the new remake of "Tsukimori," but the actress playing her mother, who played Mio in the original, demands that Kyoko pass an acting test to show she can do the role justice.